2022
DOI: 10.3389/fmicb.2021.788709
|View full text |Cite
|
Sign up to set email alerts
|

Hyunsoonleella sp. HU1-3 Increased the Biomass of Ulva fasciata

Abstract: Green algae are photosynthetic organisms and play an important role in coastal environment. The microbial community on the surface of green algae has an effect on the health and nutrition of the host. However, few species of epiphytic microbiota have been reported to play a role in promoting the growth of algae. In this study, 16S rDNA sequencing was used to study the changes of microbial composition on the surface of Ulva fasciata at different growth stages. Some growth promoting bacteria were identified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…The speci c effects of the SynCom2 of these four of these strains on the growth of U. fasciata were tested by co-culture experiment. Interestingly, H.ulvae HU1-3 alone can signi cantly promoted U.fasciata biomass accumulation in another study [45] but SynCom of ve strains including HU1-3 did not increase the biomass. The SynCom strains of 29 strains had almost the same effect as the 28 strains after removing H.ulvae HU1-3 (results not shown), We selected a mixture of 29 strains (SynCom1) as positive control to demonstrate the effectiveness of the synthetic method.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The speci c effects of the SynCom2 of these four of these strains on the growth of U. fasciata were tested by co-culture experiment. Interestingly, H.ulvae HU1-3 alone can signi cantly promoted U.fasciata biomass accumulation in another study [45] but SynCom of ve strains including HU1-3 did not increase the biomass. The SynCom strains of 29 strains had almost the same effect as the 28 strains after removing H.ulvae HU1-3 (results not shown), We selected a mixture of 29 strains (SynCom1) as positive control to demonstrate the effectiveness of the synthetic method.…”
Section: Discussionmentioning
confidence: 90%
“…Although this was not the highest in network analysis, based on the changes of bacterial abundance under different nitrogen concentrations (Fig. 1) and the species of pure bacteria were obtained [13]. Therefore, we choose Rhodobacteraceae and Flavobacteriaceae as the basis of synchronization, and their evolutionary relationship is shown in Fig.…”
Section: The Connection Between Various Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…While studies have identified the bacteria required for Ulva development [ 1 , 150 , 151 ], studies identifying specific bacteria influencing the growth of mature thallus and the biochemical composition of the biomass are still lacking. To date, a limited number of studies have attempted to demonstrate that certain bacteria can promote Ulva growth [ 167 , 168 ] and can affect the biochemical composition of Ulva [ 116 ]. Further, examination of the molecular mechanisms driving Ulva : microbial interactions is still limited.…”
Section: Strategies To Improve Ulva Biomass Yield ...mentioning
confidence: 99%
“…In sustainable agriculture, addition of plant-growth promoting bacteria has been shown to reduce the need for chemical fertilizers in terrestrial agricultures (21). Similarly, addition of specific bacterial taxa can increase growth rates of microalgae (22,23) and the macroalga Ulva (24), and many bacteria associated with marine algae produce the plant growth hormone Indole-3-acetic acid (IAA) (25)(26)(27). Bacterial inoculants are also being developed in finfish and shellfish aquaculture to protect against pathogens and increase growth rates (28)(29)(30), and in corals are a strategy for increasing tolerance to high temperature stress (31).…”
Section: Introductionmentioning
confidence: 99%